Pedagogy of Human Rights Education in an Elementary School of New Delhi: Probing the Role of Social Science Teachers - Anamika (Voices of Teachers and Teacher Educators, 2018)
Human Rights(HR) education can be introduced at all levels. The elementary level Social Science education is crucial for the development of the concept of human rights among adolescents. The pedagogy of human rights education can be a useful and effective way of inculcating deliberative methods, humane and judicious values, and rational and critical thinking among pupils. The present study is an attempt to assess social science teachers’ pedagogy in the context of human rights education. The issues germane to the study are framed through a series of questions on self perception of teachers, praxis, obstacles and pedagogy. The issues are examined with a set of three teachers of sixth grade and their classes in an elementary school of New Delhi. The findings of this study suggest that the agency of the teacher is crucial for successful implementation of HRE; that a teacher has to have passion and commitment for HR; that the rights of students as individuals must be respected by the teachers; that HRE must be context specific;that the Universal Declaration of Human Rights can be used as a universal standard to teach HR.